Asphyxie Perinatale Au Service De Neonatologie De L’hopital De La Paix De Ziguinchor (Senegal) - L., Thiam; A., Dramé; IZ., Coly; FN., Diouf; A., Sylla; O., Ndiaye (European Scientific Journal, ESJ, 2017)
Introduction: Perinatal asphyxia (PA) is one of the reasons for the transfer of the newborn to neonatal resuscitation services. The objective of this work was to study the epidemiological, obstetrical, clinical and evolutionary aspects of PA at the Ziguinchor Peace Hospital. Materials and methods: This was a retrospective study of cases of hospitalized HAs during the period 1 December 2015 to 31 May 2017. The diagnosis of PA was based on an anomaly of the rhythm Fetal heart rate and / or amniotic fluid abnormality; A score of Apgar <7 at the 5th minute and / or the absence of an immediate cry at birth. We collected epidemiological, obstetric, clinical and evolutionary data. Results: We collected 153 cases of PA (90 boys and 63 girls) among 742 newborns, an incidence of 20.6% of neonatal hospitalizations. The mean age of mothers was 17.2 years; 82.0% of mothers were between 18 and 35 years of age and half (50.3%) had four or more NPCs. Anemia (37.0%), maternal infection (36.4%), hypertension (30.9%), premature rupture of membranes (RPM) (28.6%), eclampsia and Preeclampsia (9.9%) were the main obstetric complications. The delivery was performed by Caesarean section in 52.3% of cases and by low procedure in 47.7% of cases. The term of birth was between 37 and 41 SA in 53.3% of the cases. The amniotic fluid (LA) was tinted in 55.7% of the cases and meconium in 12.3%. At the 5th minute, 42.6% of the infants had an Apgar score <7. One hundred percent of the children (n = 153) had been aspirated at birth and 24.8% (n = 38) had been ventilated To the mask. One hundred and twenty-three patients (80.3%) had anoxo-ischemic encephalopathy, of which 95 (77.2%) were in stage 1; 27 (22.0%) were in stage 2 and 1 (0.8%) was in stage 3 of the Sarnat classification. The main neurological signs were the anomalies of archaic reflexes (64.2%); Tone disorders (57.7%); Disorders of consciousness (22.8%); Convulsions (21.9%). The case fatality rate was 10.4% (16 deaths). Deaths were significantly associated with low birth, MMP, mask ventilation, respiratory distress, and convulsion. Conclusion: PA accounts for 20.6% of neonatal hospitalizations at the Ziguinchor Peace Hospital. Its lethality is 10.4%. It is associated with high morbidity.